German patent for the production of activated carbon - Germany. Reichspatentamt (1929)
German patent #484056 for the production of activated carbon, awarded to Ernst Berl (1877-1946).
Keywords: Patents; Berl, Ernst, 1877-1946; Carbon, Activated; Germany. Reichspatentamt